Late-onset and relapsed cytokine release syndrome after nivolumab treatment in a patient with head and neck squamous cell carcinoma: a case report - Otsuka, Tomoyuki; Kojitani, Yoshiki; Imamura, Fumio; Fukutake, Junko; Nishio, Minako; Fujii, Takashi; Kudo, Toshihiro (Frontiers in Oncology, 2025)
Nivolumab, an anti-programmed death-1 (PD-1) receptor monoclonal antibody, has proven effective in treating platinum-resistant metastatic head and neck squamous cell carcinoma. Immune-related adverse events (irAEs) are well-known complications of PD-1 inhibitors. Meanwhile, cytokine release syndrome (CRS), a life-threatening immune-related adverse event, rarely develops due to nivolumab monotherapy. Here, we report a case of a 65-year-old man with squamous cell head and neck carcinoma of an occult primary origin who developed nivolumab-associated late-onset CRS that recurred. The patient was admitted with symptoms of fatigue, fever, hypotension, and respiratory distress. The diagnosis of CRS was supported by the elevated serum levels of interleukin-6 and ferritin, and the patient responded well to high-dose methylprednisolone. CRS recurred during steroid tapering, coinciding with an increased tumor burden; however, it was successfully managed with increased steroid dosing. Early detection and treatment with steroids are essential for the management of CRS.